Novel Polar Coded MIMO Power Domain NOMA Scheme for 5G New Radio (NR) - Pavithra, B; Chakraborty, Parnasree (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
The use of Polar coded Multiple Input Multiple Output Power Domain Non-Orthogonal Multiple Access (MIMO PD-NOMA) technology has the potential to greatly improve the capacity and spectral efficiency of 5G NR systems. From the on-going research, there is a combination of polar coded NOMA and Polar coded MIMO techniques are approached separately with other channel coding techniques. This paper introduces a novel approach to combine polar coded with MIMO power domain NOMA to enhance the system performance. MIMO Power Domain NOMA that utilizes polar codes for channel coding and power allocation. By combining the benefits of NOMA and MIMO, which permits multiple users to share frequency-time resources simultaneously and the MIMO employs multiple antennas to increase diversity gain and spatial multiplexing gain. The proposed scheme provides effective utilization of radio resources where the polar codes are an optimal choice for 5G NR systems due to their strong error correction capability and low complexity decoding. Successive Cancellation List -Singular Value Decomposition adaptive scaling algorithm (SCL-SVD) is proposed in the polar decoding process. The suggested method attains 6.5 dB coding gain and improved throughput of 80.34% using MATLAB simulation. The proposed model compared with the other existing model such as Power Domain NOMA (PD-NOMA), multiple input single output NOMA (miso-NOMA) and multiple input multiple output NOMA (mimo-NOMA) in terms of Bit Error Rate (BER) and Signal to Noise Ratio (SNR). This scheme has the potential for practical implementation and can play a crucial role in meeting the increasing demands of future wireless communication systems.